2016
DOI: 10.1016/j.tplants.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Homoeologs: What Are They and How Do We Infer Them?

Abstract: The evolutionary history of nearly all flowering plants includes a polyploidization event. Homologous genes resulting from allopolyploidy are commonly referred to as ‘homoeologs’, although this term has not always been used precisely or consistently in the literature. With several allopolyploid genome sequencing projects under way, there is a pressing need for computational methods for homoeology inference. Here we review the definition of homoeology in historical and modern contexts and propose a precise and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
130
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(136 citation statements)
references
References 102 publications
0
130
0
1
Order By: Relevance
“…Analyzing these NWG genomic data revealed thousands of genome-wide SNP markers for its genetic diversity analysis. Thus, it is technically possible to sample genome-wide genetic variability in plants with complex genomes through GBS, even though SNP calling from sequences of a complex, polyploid genome is confounded by the presence of homeologs [54], orthologs, and paralogs [55]. Thousands of SNP markers would be more informative for plant genetic diversity analysis with higher resolution than the several hundreds of AFLP markers normally screened in previous studies [50,51,56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing these NWG genomic data revealed thousands of genome-wide SNP markers for its genetic diversity analysis. Thus, it is technically possible to sample genome-wide genetic variability in plants with complex genomes through GBS, even though SNP calling from sequences of a complex, polyploid genome is confounded by the presence of homeologs [54], orthologs, and paralogs [55]. Thousands of SNP markers would be more informative for plant genetic diversity analysis with higher resolution than the several hundreds of AFLP markers normally screened in previous studies [50,51,56,57].…”
Section: Discussionmentioning
confidence: 99%
“…‘Homoeologous exchanges’ specifically describe exchanges of large chromosomal segments that result from crossover formation between homoeologous chromosomes (i.e. inherited from divergent parental species and re‐united within a single allopolyploid genome; Glover et al ., ) via the meiotic homologous recombination pathway (Sharpe et al ., ; Gaeta & Pires, and references therein). This type of event is thus unique to allopolyploids and frequent in the first generations following allo‐polyploidisation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1B;Manton, 1950;Wagner & Chen, 1965;Hickok & Klekowski, 1974;Wagner, 1974;Hickok, 1977;Reichenstein, 1981). Rare, completely fertile homoploid hybrids, such as Pteris quadriaurita  multiaurita reported by Walker (1958Walker ( , 1962, result from crosses between sexual species with low genetic divergence and exhibit full pairing of homoeologs (i.e., chromosome copies derived from different progenitor species; Glover et al, 2016) at meiosis. Additional studies have reported homoploid hybrids with spore germination rates as high as 29-40% and gametophytes producing functional sperm and/or eggs (Walker, 1958(Walker, , 1962Whittier & Wagner, 1971;Bierhorst, 1977;Conant, 1990;Mayer & Mesler, 1993;Mullenniex et al, 1998).…”
Section: Homoploid Hybridsmentioning
confidence: 99%